2016
DOI: 10.1515/acs-2016-0017
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant effectiveness of dehydrogenated p-phenylene diamines through NMR calculations

Abstract: NMR shifts of N-phenyl-N'-alkyl-p-phenylenediamines (PPD) in vacuum were evaluated by B3LYP calculations using GIAO method. According to our previous studies, the Molar Antioxidant Effectiveness (AEM) of PPD antioxidants correlates with NMR chemical shifts of the amine nitrogen between aromatic rings (N A ), the side aliphatic chain nitrogen (N B ) and its neighboring tertiary carbon atom (C T ) as well as of the hydrogens bonded to them. Our results indicate that the above mentioned chemical shifts correlate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…T A B L E 2 Absolute (E DFT ) and relative DFT energy (ΔE DFT ) of antioxidants (R Aox H 2 ), as well as of their single (R Aox H) and double (R Aox ) dehydrogenated products in their ground spin states of multiplicity M S obtained at the B3LYP/6-311G* level of theory (relative DFT energies are related to R Aox H 2 , the most stable R Aox H and R Aox species are indicated in bold) [66] Compound Puskarova et al [72] observed a linear relationship between NMR chemical shifts of N (and the corresponding H) atoms in deuterated dimethyl sulfoxide solutions and AEM values of antioxidants DPPD, SPPD, 6PPD and IPPD in PIR matrices. We reproduced their results for a larger set of DPPD, IPPD, MBPPD, 6PPD, p-c6PPD and o-c6PPD in SBR and PIR at 180 C (see Table 1) using analogous B3LYP/6-311G* calculations [73] based on the re-optimization of the most stable PM3 conformations [61] using Gaussian09 software.…”
Section: Bond Dissociation Enthalpiesmentioning
confidence: 99%
See 1 more Smart Citation
“…T A B L E 2 Absolute (E DFT ) and relative DFT energy (ΔE DFT ) of antioxidants (R Aox H 2 ), as well as of their single (R Aox H) and double (R Aox ) dehydrogenated products in their ground spin states of multiplicity M S obtained at the B3LYP/6-311G* level of theory (relative DFT energies are related to R Aox H 2 , the most stable R Aox H and R Aox species are indicated in bold) [66] Compound Puskarova et al [72] observed a linear relationship between NMR chemical shifts of N (and the corresponding H) atoms in deuterated dimethyl sulfoxide solutions and AEM values of antioxidants DPPD, SPPD, 6PPD and IPPD in PIR matrices. We reproduced their results for a larger set of DPPD, IPPD, MBPPD, 6PPD, p-c6PPD and o-c6PPD in SBR and PIR at 180 C (see Table 1) using analogous B3LYP/6-311G* calculations [73] based on the re-optimization of the most stable PM3 conformations [61] using Gaussian09 software.…”
Section: Bond Dissociation Enthalpiesmentioning
confidence: 99%
“…The relative stability of the dehydrogenation products obtained by hydrogen abstraction from various active sites of PPD antioxidants was studied by semiempirical as well as by DFT methods. [60][61][62][63][64][65][66] Table 2 presents the most recent B3LYP/6-311G* results for selected PPD antioxidants (R Aox H 2 ), their single (R Aox H) and double (R Aox ) dehydrogenated products as well [66] based on the reoptimization of the most stable PM3 conformations [61] using Gaussian03 software. [67] They are in agreement with the conception based on the preferred formation of stable ketimine Ph-N=C structures (instead of the quinonediimine ones) during step-by-step dehydrogenation despite the N A centered radicals formed in the 1st step of dehydrogenation are more stable.…”
Section: Antioxidant Effectivenessmentioning
confidence: 99%